2013
DOI: 10.1136/bjophthalmol-2013-304349
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of macular ganglion cell layer and peripapillary retinal nerve fibre layer thickness changes after panretinal photocoagulation

Abstract: The macular GCIPL and peripapillary RNFL thickness increased throughout the 1-year post-PRP. Furthermore, the macular GCIPL and temporal RNFL thickness showed a significant correlation throughout the 1 year of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
3
19
0
2
Order By: Relevance
“…Transitory increases in macular GCIPL and peripapillary RNFL thicknesses throughout the 1year post-PRP follow-up were found in a prospective, interventional case series study of 35 eyes. 16 These data could be explained by PRP-induced retinal inflammation and edema in the early post-PRP phase, secondary to early glial cell activation. In our study, all patients had received previous PRP more than 6 months before, so that should not have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…Transitory increases in macular GCIPL and peripapillary RNFL thicknesses throughout the 1year post-PRP follow-up were found in a prospective, interventional case series study of 35 eyes. 16 These data could be explained by PRP-induced retinal inflammation and edema in the early post-PRP phase, secondary to early glial cell activation. In our study, all patients had received previous PRP more than 6 months before, so that should not have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological parameters remained stable across all retinopathy levels regardless of whether the laser-treated patients were included in the analysis. Panretinal photocoagulation, however, has been shown to induce retinal thickening in both the peripapillary and macular regions, at least during the first year after treatment [ 42 ]. Several studies have demonstrated decreased retinal thickness with age [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the high-resolution OCT system, we found the transient increase of ONL thickness and the decrease of OLM/RPE complex thickness at the earliest time point after laser photocoagulation. Whereas scatter laser photocoagulation was reported to progressively reduce the thickness of the inner retina in patients with DME, [29][30][31] transient ONL thickening at 1 day after laser photocoagulation was also documented in patients with DME. 32 Furthermore, Mitsch et al.…”
Section: Discussionmentioning
confidence: 99%